Multifunctional micro/nano-textured titanium with bactericidal, osteogenic, angiogenic and anti-inflammatory properties: Insights from in vitro and in vivo studies - Théo Ziegelmeyer; Karolinne Martins de Sousa; Tzu-Ying Liao; Rodolphe Lartizien; Alexandra Delay; Julien Vollaire; Véronique Josserand; Denver Linklater; Phuc H. Le; Jean-Luc Coll; Georges Bettega; Elena P. Ivanova; et al. (Materials Today Bio)
Titanium (Ti) is widely used as an implantable material for bone repair in orthopedics and dentistry. However, Ti implants are vulnerable to bacterial infections, which can compromise patient recovery and lead to implant failure. While a controlled inflammatory response promotes bone regeneration, chronic inflammation caused by infections can lead to implant failure. Bone repair is a complex process in which inflammation, angiogenesis and osteogenesis are tightly interconnected, requiring cooperation between mesenchymal stem cells (MSC), macrophages and endothelial cells. Here, we fabricated bio-inspired Ti implants with either microstructured (Micro Ti) or nanostructured (Nano Ti) surface textures that exhibit robust mechano-bactericidal properties. In vitro, both textured surfaces improved blood coagulation and osteogenic marker expression compared to smooth Ti surfaces. Additionally, Nano Ti promoted macrophage polarization towards the M2 phenotype and enhanced the paracrine effects of MSCs on angiogenesis, key processes in tissue regeneration. In vivo kinetic analysis of bone reconstruction in a rat calvarial model showed that Nano Ti improved osseointegration, as evidenced by increased bone volume, mineral density, and bone-implant contact. Notably, the Micro Ti surface showed no significant differences from the control implants. These findings highlight the potential of mechano-bactericidal surface nanopatterns to simultaneously prevent infections and enhance osseointegration by modulating protein adsorption, inflammation, angiogenesis and osteogenesis. This study provides new insights into the development of bifunctional Ti implants, offering new perspectives for the next generation of implantable bone-related biomaterials.